Pain assessment and analgesia in pre-admission care of trauma patients. - Calil, Ana Maria (2008)
Pain is one of the main complaints at admission in emergency services. This article aims at presenting pain assessment methods in trauma patients using objective tools in pre- and intra-hospital settings. The harmful effects of pain in the posttrauma patients, and the benefits of early analgesia are discussed. We found that acute pain in emergency wards is rarely studied in Brazil, which points out a significant gap in terms of care and research.